From knights to pioneers : one German family in Westphalia and Missouri - Mallinckrodt, Anita M. (Southern Illinois University Press, 1994)
Emil and Julius Mallinckrodt (cousins) left Dortmund, Germany in 1831, sailing from LeHavre, France to New Orleans and thence to Missouri. This historical work covers mainly the U.S. period in Missouri 1831-1890. The family originated in the Dortmund area, the first known ancestor being Knight Ludwig, first recorded in 1241.